2022
DOI: 10.1002/alz.12638
|View full text |Cite
|
Sign up to set email alerts
|

2022 Alzheimer's disease facts and figures

Abstract: This article describes the public health impact of Alzheimer's disease (AD), including incidence and prevalence, mortality and morbidity, use and costs of care, and the overall impact on family caregivers, the dementia workforce and society. The Special Report discusses consumers' and primary care physicians' perspectives on awareness, diagnosis and treatment of mild cognitive impairment (MCI), including MCI due to Alzheimer's disease. An estimated 6.5 million Americans age 65 and older are living with Alzheim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
664
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,550 publications
(795 citation statements)
references
References 648 publications
(1,384 reference statements)
7
664
2
Order By: Relevance
“…From a public health perspective, optimizing dementia care in the home may provide the maximum population-level benefit (such as decreasing the huge economic costs associated with transitions to other care settings) and is desirable given the preference of older people to remain in their familiar communities for as long as possible ( 48 ). The majority of older people with dementia live at home with unpaid family caregivers, and these family caregivers are at risk for poor physical, mental, emotional, and socioeconomic outcomes ( 49 ). The present study found that family caregivers caring for community-dwelling older people with dementia were exposed to more frequent clinically significant and moderate-severe distressing BPSD than formal caregivers (nursing home staff).…”
Section: Discussionmentioning
confidence: 99%
“…From a public health perspective, optimizing dementia care in the home may provide the maximum population-level benefit (such as decreasing the huge economic costs associated with transitions to other care settings) and is desirable given the preference of older people to remain in their familiar communities for as long as possible ( 48 ). The majority of older people with dementia live at home with unpaid family caregivers, and these family caregivers are at risk for poor physical, mental, emotional, and socioeconomic outcomes ( 49 ). The present study found that family caregivers caring for community-dwelling older people with dementia were exposed to more frequent clinically significant and moderate-severe distressing BPSD than formal caregivers (nursing home staff).…”
Section: Discussionmentioning
confidence: 99%
“…An estimated 6.5 million people are living with Alzheimer’s disease (AD) in the United States, and the number of affected individuals is expected to double by 2050. 2 Despite the rising prevalence, a cure for AD is still not available because of its complex nature. 2 Although the mechanism of disease pathology is widely debated; AD is pathologically distinguished by the accumulation of amyloid β (Aβ) in senile plaques and tau into hyperphosphorylated neurofibrillary tangles.…”
Section: Main Textmentioning
confidence: 99%
“… 2 Despite the rising prevalence, a cure for AD is still not available because of its complex nature. 2 Although the mechanism of disease pathology is widely debated; AD is pathologically distinguished by the accumulation of amyloid β (Aβ) in senile plaques and tau into hyperphosphorylated neurofibrillary tangles. 3 In addition, aggregates of other amyloidogenic proteins, such as TAR DNA-binding protein-43 (TDP-43) and α-synuclein, have also been found in AD, complicating its etiological landscape.…”
Section: Main Textmentioning
confidence: 99%
“…Alzheimer disease, * the most common cause of dementia, affects an estimated 6.5 million persons aged ≥65 years in the United States ( 1 ). A growing body of evidence has identified potential modifiable risk factors for Alzheimer disease and related dementias (ADRD) ( 1 – 3 ).…”
mentioning
confidence: 99%
“…Alzheimer disease, * the most common cause of dementia, affects an estimated 6.5 million persons aged ≥65 years in the United States ( 1 ). A growing body of evidence has identified potential modifiable risk factors for Alzheimer disease and related dementias (ADRD) ( 1 – 3 ). In 2021, the National Plan to Address Alzheimer's Disease (National Plan) introduced a new goal to “accelerate action to promote healthy aging and reduce risk factors for Alzheimer’s disease and related dementias” to help delay onset or slow the progression of ADRD ( 3 ).…”
mentioning
confidence: 99%